2013
DOI: 10.1002/ppsc.201300194
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Asymmetric Porous Janus Particles Using Microfluidics and Directional UV Curing

Abstract: Asymmetric porous Janus particles of poly(tripropylene glycol diacrylate) poly(TPGDA)) are prepared from TPGDA/4‐cyano‐4′‐pentylbiphenyl (5CB) mixtures using microfluidics and directional ultraviolet (UV) curing. Droplets of the TPGDA/5CB mixtures, which have been prepared successfully in the microfluidics channel, are photo‐polymerized in the off‐chip reservoir with a focused UV beam irradiated from beneath the reservoir. The isotropic TPGDA/5CB single phase is phase‐separated into two phases during the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Nonspherical colloidal particles with asymmetric structures and different chemical functionalities have been widely researched because of their development prospects as functional surfactants, , compatibilizers, coatings, and catalysts . To date, various methods for the syntheses of asymmetric particles have been proposed, including microfluidic technique, toposelective modification, Pickering emulsion polymerization, seeded emulsion polymerization, self-assembly, controlled phase separation, , and surface nucleation . Among these, seeded emulsion polymerization has been proved to be efficient and flexible to prepare snowman-like, raspberry-like, and other nonspherical composite particles …”
Section: Introductionmentioning
confidence: 99%
“…Nonspherical colloidal particles with asymmetric structures and different chemical functionalities have been widely researched because of their development prospects as functional surfactants, , compatibilizers, coatings, and catalysts . To date, various methods for the syntheses of asymmetric particles have been proposed, including microfluidic technique, toposelective modification, Pickering emulsion polymerization, seeded emulsion polymerization, self-assembly, controlled phase separation, , and surface nucleation . Among these, seeded emulsion polymerization has been proved to be efficient and flexible to prepare snowman-like, raspberry-like, and other nonspherical composite particles …”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the preparation of functionalized LC droplets, in which steadystate droplet break-off in the microuidics channel was used to create monodisperse 5-cyanobiphenyl (5CB, a nematic LC at room temperature) droplets in water. [10][11][12][13] A droplet was formed at the channel junction. Its size was controlled by the competition between viscous drag and surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the droplet hemisphere directly facing UV radiation swelled (and wrinkled when dried), while the other hemisphere remained smooth making the particle asymmetrically porous. 62 Li et al altered the contents of the dispersed phase from an organochloride compound (dichloromethane) to an organic compound (dimethyl carbonate) for phase separation-based Janus particle synthesis. They concluded that by changing the nature of the dispersed phase from an organochloride to an organic fluid, a morphology transition from core-shell microcapsule to Janus could be achieved.…”
Section: Phase Separationmentioning
confidence: 99%